Primary ovarian leiomyoma with predominant cystic change - Tatsunori Asada, MD, PhD (Radiology Case Reports, 2019)
Ovarian leiomyoma is a rare benign tumor, seen mostly in women 20-65 years old. The case of a 51-year-old woman with a large tumor in the pelvic cavity is reported. The dominant feature of the tumor was its cystic component, but an irregular, solid component was recognized along the dorsal margin of the tumor. The latter area showed signal intensity as low as muscle on T2-weighted images and significant contrast enhancement; however, it did not show restricted diffusion, which implied that it was benign. The large tumor was resected because malignancy could not be ruled out, and it was pathologically diagnosed as ovarian leiomyoma with predominant necrosis. When a low-intensity component without malignant features is seen on magnetic resonance imaging, leiomyoma should be included in the differential diagnosis despite its rare occurrence in the ovary. Keywords: Ovarian leiomyoma, Cystic component, Solid component, Magnetic resonance imaging